IMPACT OF SOIL AND WATER CONSERVATION WORKS ON GROUND WATER REGIME IN KANDI AREA OF PUNJAB - Khepar, S.D.; Sondhi, S.K.; Chawla, J.K.; singh, Mandeep (Journal of Soil and Water Conservation, 2022)
The intensive agriculture in the state of Punjab has resulted into over- exploitation of ground water resources leading to decline in water-table, almost in the entire sweet ground water zone. The decline in water-table can be checked by reducing the ground water draft and/or increasing the ground water recharge. The availability of good quality water and suitable sites are pre-requisite for ground water recharge. Both these conditions are fulfilled in the Kandi area of Punjab. The runoff during monsoon could be used for ground water recharge in the Kandi area, resulting in arresting the decline in water-table in the lower reaches. A large number of soil and water conservation works under the World Bank Aided Project "Kandi Watershed Area Development Project" were constructed in this area. The impact of these works on ground water regime has been investigated The studies have revealed that the water-table in Hoshiarpur district has been rising on an average of 2.26 cm/year during the period 1979- 98 as a result of these works. The study emphasized the need for taking up the watershed management works in the upper reaches of declining water-table areas on priority basis for reversing the trend of declining water-table.